Situation Report: Poland, 23 January 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Meeting of Polish and Soviet Leaders Rapacki's Forthcoming Visit to Paris Church and State Officials Discuss Seminaries Conference of People's Councils' Chairmen Trade Talks with Iran and Kuwait Polish-Japanese Trade Talks Scheduled Polish-Cuban Trade Protocol Polish-Czechoslovak Trade Protocol Brazilian Trade Delegation in Warsaw